Chapter La signoria di Arena in Oltrepò. I Beccaria e la forza della comunità (secoli XIII-XVI) - Covini, Maria Nadia (Firenze University Press, 2022)
The lordship of the Beccaria, a branch of the great family from Pavia, on Arena Po, was established at the end of the thirteenth century, taking advantage of both the financial difficulties of the small municipality and the power of the family in Pavia. It was meant to last for centuries. Managed in a consortium form by various Beccaria exponents, it encountered difficulties also in relation to the political events of the duchy. Various documents are examined to investigate the nature, modalities and reality of the relations between the lords and the land in the final centuries of the Middle Ages, especially from the fiscal, economic and agricultural point of view.